2010
DOI: 10.1590/s1809-29502010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da aromaterapia na redução de níveis de estresse e ansiedade em alunos de graduação da área da saúde: estudo preliminar

Abstract: Este estudo teve como objetivo verificar a eficácia de aromaterapia na diminuição de níveis de estresse e ansiedade (traço e estado) de alunos de graduação de cursos na área da saúde. Participaram do estudo 36 sujeitos, com idade entre 18 e 29 anos, que foram divididos entre os que receberam tratamento (grupo aroma, n=18) e o grupo controle (n=18). Os sujeitos foram avaliados quanto a níveis de estresse e ansiedade antes e após o período de intervenção, pela Lista de Sintomas de Estresse e pelo Inventário de A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 10 publications
2
5
0
20
Order By: Relevance
“…However, when dealing with psychological aspects, the measurements showed no effect on stress. These results corroborate those found in previous studies that demonstrated the effectiveness of aromatherapy only in physiological parameters (10,12,(20)(21) .…”
Section: Discussionsupporting
confidence: 92%
“…However, when dealing with psychological aspects, the measurements showed no effect on stress. These results corroborate those found in previous studies that demonstrated the effectiveness of aromatherapy only in physiological parameters (10,12,(20)(21) .…”
Section: Discussionsupporting
confidence: 92%
“…It is believed that this result is attributed to the emotional effects via the olfactory bulb and and a depressesion of the central nervous system. 23 Reaffirming the data presented in this study, the scientific literature shows an exponential increase in the use of non-conventional health practices for the treatment of various acute and chronic diseases, among these we can highlight cancer. 14 Thus, the use of non-conventional practices in health is directly related to physical and emotional pain relief, and it also promotes increased quality of life.…”
Section: Resultssupporting
confidence: 84%
“…A aromaterapia também tem sido apontada como um mecanismo para a redução de estresse e ansiedade. Os tratamentos são realizados à base de óleos que atuam diminuindo a pressão arterial e aumentando a temperatura da pele, com um consequente efeito calmante e relaxante, reduzindo até 24% dos níveis de estresse 54 .…”
Section: Discussionunclassified